The Implementation of Think Pair Share (TPS) Type of Cooperative Learning Model To Improve Student’s Motivation And Nutrition Science Learning Achievement - Sukelasmini, I Gusti Ayu Made (Journal of Education Action Research, 2019)
The purpose of this research is to know the increasing of student’s motivation and nutrition science learning achievement at second semester Grade X students of SMK N 2 Singaraja Academic Year 2016/2017 after applied the model of Think Pair Share type of cooperative learning model. This research is a classroom action research (CAR). The subjects in this classroom action research are the second semester students of Class X of Tata Boga 5 SMK N 2 Singaraja academic year 2016/2017 which amounts of 41 students. While the object is motivation and student learning achievement. Students' motivational data were collected with observation sheets, while student learning achievement were collected with multiple choice tests. Data analysis used in this research is descriptive data analysis. Based on the research that has been done, it can be concluded that the TPS type cooperative learning model can effectively improve the motivation and learning achievement of Nutrition science at second semester grade X students 5 SMK N 2 Singaraja academic year of 2016/2017. This is evident from the average improvement in student learning motivation in cycle I of 22.10 to 25.22 in cycle II. Classical completeness in cycle I of 82.93 increased to 95.12 in cycle II. While the average increase in student learning results in cycle I was 24.32 increased to 30.41 in cycle II. Classical completeness at cycle I of 78.05 increased to 100 in cycle II